Biological activity of protein antigens isolated from Mycobacterium tuberculosis culture filtrate. - Collins, F M (1988)
Mycobacterium tuberculosis culture filtrate (MTCF) protein antigens were isolated from mid-logarithmic-phase cultures grown in liquid medium and examined by high-pressure liquid chromatography and Western blot (immunoblot) analysis. A major protein band with a molecular mass of about 68 kilodaltons (kDa) and several fainter bands in the 38- and 24-kDa range were observed. The MTCF protein produced a significant delayed footpad hypersensitivity response in Mycobacterium bovis BCG-vaccinated C57BL/6 mice, comparable to that observed with standard purified protein derivative (PPD). The same proteins induced a blastogenic response in tuberculin-sensitive human peripheral blood monocytes and in T-cell clones developed from these cells. The proliferative responses to the MTCF antigens were equivalent to those observed following stimulation with PPD or M. tuberculosis sonic extracts. However, the MTCF sensitins were not recognized by five monoclonal antibodies directed against killed M. tuberculosis antigens in an enzyme immunoassay, although some response was seen with a monoclonal antibody (ML34) directed against M. leprae antigens. The ability of the MTCF to stimulate T-cell responses both in vivo and in vitro while not being recognized by antibodies directed against dead mycobacterial antigens suggests that they may be of interest as potential protective immunogens.